The Influence of Online and Offline Sales at Marina Bakoel Klambi Shop - Rahmadi, Rahmadi; Dewi, Intan Kusuma (Asosiasi Dosen Akuntansi Indonesia, 2023)
The current level of intense business competition forces businesspeople to continue trying to maintain their operations and compete to achieve predetermined goals. Now, selling products involves more than just offline sales or so-called traditional sales, but also utilizing information technology. Toko Marina Bakoel Klambi is faced with the problem of sales methods. Whether to stay focused on traditional methods or use information technology in the present, this study uses quantitative methods using multiple linear regression analysis in software in the form of SPSS 25 tools. Based on the results of the analysis at the 0.05 significance level, it shows that sales so far have a significant effect on the level of sales. Conversely, it can be proven that offline sales do not influence the level of sales. In addition, in the simultaneous significance test offline and during sales have a significant impact on the number of sales. So, in this case, the comparison of sales at Toko Marina Bakoel Klambi in terms of time is more useful for sellers in boosting sales